2014
DOI: 10.3390/ijerph110303118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heavy Metals and PCBs Pollution on the Enzyme Activity and Microbial Community of Paddy Soils around an E-Waste Recycling Workshop

Abstract: Due to the emerging environmental issues related to e-waste there is concern about the quality of paddy soils near e-waste workshops. The levels of heavy metals and PCBs and their influence on the enzyme activity and microbial community of paddy soils obtained from the immediate vicinity of an e-waste workshop were investigated in the present study. The results indicated that the heavy metal and PCB pollution did not differ significantly with an increase of the sampling point distances (5 to 30 m). The concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…fertilizer, pesticides, and herbicides) [16,17]. On the other hand, correlation analysis showed that heavy metals have significantly correlated each other except for Cr ( Table 4), suggesting that they might have similar pollution sources [32,33]. Moreover, the nutrient is significantly positively related to heavy metals (except Cr) ( Table 4), suggesting that enrichment of the nutrient may be a reason for richer heavy metals in sediment of the riparian zone in the TGR.…”
Section: Assessment Of Heavy Metal Contamination 2255mentioning
confidence: 95%
“…fertilizer, pesticides, and herbicides) [16,17]. On the other hand, correlation analysis showed that heavy metals have significantly correlated each other except for Cr ( Table 4), suggesting that they might have similar pollution sources [32,33]. Moreover, the nutrient is significantly positively related to heavy metals (except Cr) ( Table 4), suggesting that enrichment of the nutrient may be a reason for richer heavy metals in sediment of the riparian zone in the TGR.…”
Section: Assessment Of Heavy Metal Contamination 2255mentioning
confidence: 95%
“…The activity of soil enzymes is often used to monitor the effects of various pollutants on microbial functioning (Turgay et al 2010, Tang et al 2014, Tomkiel et al 2015. In the tested soils, the activities of a range of enzymes contributing to the biogeochemical cycle of carbon, nitrogen and phosphorus were determined (Fig.…”
Section: Enzyme Activitymentioning
confidence: 99%
“…Using the DGGE method, the distribution and diversity of bacteria were measured using the Shannon-Weiner and Simpson indices. Tang et al 39 investigated the influence of heavy metals and PCBs on the microbial community of paddy soils and showed that the level of heavy metal and PCB pollution had a minor influence on bacterial community structure in paddy soils. Hassanshahian 40 also found that bacteria isolated from uncontaminated sites have higher diversity compared to those from contaminated sites.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological structure and diversity of bacterial communities in anthropogenically polluted environments are good indicators 39 and important prerequisites for bioremediation of organic contaminants. Screening and isolation of target bacteria and genes from rhizosphere soil or plant tissues, and then using them to remove PAHs from soils 45 , can effectively reduce the risk of plant organic contamination 8 46 and protect food security, as well as human health.…”
Section: Discussionmentioning
confidence: 99%